Case Report: Early detection of pancreatic pre-cancer lesion in multimodal approach with exosome liquid biopsy - Dhani, Harmeet; Hinestrosa, Juan Pablo; Izaguirre-Carbonell, Jesus; Balcer, Heath I.; Kurzrock, Razelle; Billings, Paul R. (Frontiers in Oncology, 2023)
BACKGROUND The detection of pancreatic ductal adenocarcinoma (PDAC) lesions at pre-cancerous or early-stages is critical to improving patient survival. We have developed a liquid biopsy test (ExoVita®) based on the measurement of protein biomarkers in cancer-derived exosomes. The high sensitivity and specificity of the test for early-stage PDAC has the potential to improve a patient’s diagnostic journey in hopes to impact patient outcomes. METHODS Exosome isolation was performed using alternating current electric (ACE) field applied to the patient plasma sample. Following a wash to eliminate unbound particles, the exosomes were eluted from the cartridge. A downstream multiplex immunoassay was performed to measure proteins of interest on the exosomes, and a proprietary algorithm provided a score for probability of PDAC. RESULTS We describe the case of a 60-year-old healthy non-Hispanic white male with idiopathic acute pancreatitis who underwent numerous invasive diagnostic procedures that failed to detect radiographic evidence of lesions. Following the detection of KRAS and TP53 mutations, the patient decided to undergo a pancreaticoduodenectomy (Whipple) procedure. Surgical pathology confirmed the diagnosis of high-grade intraductal papillary mucinous neoplasm (IPMN), in line with our exosome-based test indicating high probability of PDAC. The patient’s post-operative course was unremarkable. At five-month follow-up, the patient continued to recover well without complications, in addition to a repeat ExoVita® test which demonstrated low probability of PDAC. CONCLUSIONS This case report highlights how a novel liquid biopsy diagnostic test based on the detection of exosome protein biomarkers allowed early diagnosis of a high-grade precancerous lesion for PDAC and improved patient outcome.